Thermal insulation and temperature regulation artificial board material for wall and manufacturing process thereof

By combining bark with mineral polymers and adding fixed phase transformer materials to prepare composite materials with excellent mild insulation effects, the deficiencies of traditional thermal insulation materials in flame retardant performance and insulation performance are solved. Environmental protection building materials.

CN119371144APending Publication Date: 2025-01-28BEIJING FORESTRY UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410799831.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-20
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

There are shortcomings in existing insulation materials between flame retardant properties and insulation properties, and traditional phase change materials are prone to changes in physical state and leakage problems when exercising the temperature regulation function.

Method used

By combining the bark with the mineral polymers, prepare a composite material with thermal insulation and temperature adjustment function, and add fixed phase transformation materials to the material to improve the temperature regulation performance. At the same time Toughness, immersion fixation and secondary packaging, improve the overall performance of the material.

Benefits of technology

The composite thermal insulation materials used in the building wall have been realized, which have excellent temperature adjustment and thermal insulation effects, and the raw materials are widely sources, low in price, and environmentally friendly, which meets the requirements of green sustainable development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371144A_ABST
    Figure CN119371144A_ABST
Patent Text Reader

Abstract

The invention discloses a novel method for compounding and preparing a thermal insulation material by using bark and a mineral polymer as raw materials. According to the invention, a foaming mineral polymer is used as a matrix, and alkali-treated pine bark powder is added to reinforce and toughen, so that the high-heat-preservation bark-mineral polymer composite foaming material is prepared; pine bark pyrolysis biomass charcoal is used for packaging and fixing a phase change material PEG1000, and a mineral polymer is used for secondary packaging, so that the mineral polymer packaged bark carbon shape-stabilized phase change material with a certain specification and size is prepared; by combining the two materials, the finally obtained composite thermal insulation wall material can further reduce the indoor temperature difference and reduce the energy consumption. The bark-mineral polymer composite wall material prepared by the invention has the advantages of low cost, high performance, greenness, low carbon, flame retardance, energy storage, cyclic utilization and the like, can be used as a building house thermal insulation wall material, and promotes green and sustainable development of the building material industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a novel composite thermal insulation wall material production and processing technology, in particular to a bark-mineral polymer composite thermal insulation wall material with thermal insulation and temperature regulation functions and a manufacturing process thereof, belonging to the field of wood processing. Background Art

[0002] Thermal insulation materials are a very important part of building materials. Traditional organic thermal insulation materials have low thermal conductivity and good thermal insulation effect, but their flame retardancy is generally poor and they may release toxic gases when burned. Inorganic thermal insulation materials have good flame retardancy, but their thermal insulation performance is poorer than that of organic thermal insulation materials. Common cement walls not only have poor thermal insulation effects, but also release a large amount of carbon dioxide during the production process. Therefore, the development of composite thermal insulation wall materials that can combine the complementary advantages of organic and inorganic materials is currently a hot topic in thermal insulation materials.

[0003] Mineral polymer is a new type of green inorganic cementitious material prepared by alkali activation using industrial waste such as kaolin, fly ash, and slag as precursors. Not only is its raw material industrial waste, which is widely available and environmentally friendly, but its production, transportation, and manufacturing also generate much less CO2 emissions than ordinary Portland cement. Foamed mineral polymer has a porous structure and good thermal insulation performance, but its compressive strength and other properties are reduced. Therefore, modifying the foamed mineral polymer to simultaneously improve its thermal insulation and mechanical properties is a key issue to be solved.

[0004] Insulation materials that only block heat transfer still have limitations. Resisting outdoor temperature changes and actively regulating indoor temperature are new trends in the development of wall insulation materials. Phase change energy storage materials that can temporarily store energy and regulate temperature changes have become a research hotspot in the current field of building insulation. However, when traditional phase change materials take effect, there are usually changes in physical state, which may cause leakage. They need to be encapsulated and shaped using porous materials or microcapsules. At present, relevant researchers have prepared shaped encapsulated phase change wall panels, and their temperature regulation performance has been verified and applied in practice, but their thermal insulation performance still needs to be improved.

[0005] Therefore, organic biomass materials and inorganic mineral polymer materials are combined to prepare composite thermal insulation materials, so that organic and inorganic materials can complement each other's advantages. At the same time, phase change materials with heat storage and temperature regulation functions are added to change the traditional thermal insulation methods. Composite thermal insulation wall materials with both thermal insulation and temperature regulation properties are prepared, which is of great significance to the reform and development of thermal insulation materials in the construction industry. Summary of the invention

[0006] The purpose of the present invention is to provide a thermal insulation and temperature regulating filling material for walls and a manufacturing process thereof. The bark-mineral polymer composite material prepared by the present invention uses bark and metakaolin as raw materials, and is prepared through alkali excitation, curing and foaming, strengthening and toughening, high-temperature pyrolysis, impregnation and fixation, secondary packaging, assembly and compounding. The bark-mineral polymer composite material has a simple manufacturing process, low production cost, and is green and environmentally friendly. It has both temperature regulating and heat preservation functions and can be used as a building wall material to promote the realization of green and sustainable development of the building materials industry.

[0007] To achieve the purpose of the present invention, on the one hand, the present invention provides a bark-mineral polymer composite insulation wall material. Under the typical spring and summer environmental conditions in Beijing, the temperature peak delay time and attenuation rate on the inner side of the material are 2.83-3.76h, 16.4-22.2% and 3.13-4.12h, 13.1-18.0%, respectively, which has good temperature regulation and insulation effects.

[0008] The bark-mineral polymer composite wall material is characterized by being composed of a foaming material and a shaped phase change material prepared from bark and mineral polymer respectively, and the mineral polymer encapsulated bark carbon shaped phase change material can be placed in three positions (outside, middle and inside) in the combined wall.

[0009] On the other hand, a method for preparing a bark-mineral polymer composite thermal insulation and temperature regulating material is provided, comprising the following steps in order:

[0010] A. Preparation of Geopolymers

[0011] Aluminosilicate is used as a precursor, and mineral polymers are obtained through alkali excitation, complexation, transfer diffusion, condensation and hardening.

[0012] B. Preparation of mineral polymer foam materials

[0013] 1) Foaming

[0014] After adding the foaming agent, stir to fully foam the mineral polymer;

[0015] 2) Strengthening and toughening

[0016] Adding alkali-treated bark to foamed mineral polymers to enhance strength and toughness;

[0017] 3) Maintenance

[0018] Carry out 48h+7d curing treatment on the foamed mineral polymer;

[0019] C. Preparation of bark carbon phase change thermal storage material

[0020] 1) High temperature pyrolysis

[0021] Pine bark was treated with KHCO3 solution to obtain dried powder, which was fully ground and then pyrolyzed in a tube furnace;

[0022] 2) Immersion fixation

[0023] The pyrolyzed bark carbon was impregnated with polyethylene glycol;

[0024] 3) Secondary packaging

[0025] Secondary encapsulation of PEG-bark with mineral polymers;

[0026] D. Bark-Geopolymer Composite Assembly

[0027] The bark-mineral polymer foaming material prepared in B is combined with the mineral polymer encapsulated bark carbon shaped phase change material prepared in C to obtain a bark-mineral polymer composite thermal insulation material.

[0028] The aluminosilicate in step A is metakaolin, and the alkali activator is prepared by mixing a sodium silicate solution and a 10 mol / L sodium hydroxide solution in a certain proportion;

[0029] The modulus of the geopolymer in step B1) is 1.3-2.1, the alkali-ash ratio is 1.3-2.5, and the foaming agent is 30% hydrogen peroxide (H2O2) with a mass fraction of 1-3wt%;

[0030] The bark added in step B2) is coniferous bark, with a moisture content of less than 10%, a mesh size of 60-100 meshes, and a mass fraction of 5wt%;

[0031] The curing conditions in step B3) are curing in a forced air drying oven at 60°C for 48 hours and then curing at room temperature for 7 days;

[0032] The bark used in step C1) has a mesh size of 80-100 mesh, and the mass ratio of the bark to the KHCO3 solution with a concentration of 0.25 mol / L is 1:15-1:20, and the bark is calcined at a temperature of 400-800°C for 2h;

[0033] Wherein the molecular weight of the PEG polyethylene glycol used for impregnation in step C2) is 1000, and the mass ratio of the PEG polyethylene glycol to the bark powder is 2:1 to 3:1;

[0034] In step C 3), the modulus of the mineral polymer material is 1.3 to 2.1, the alkali-ash ratio is 1.3 to 2.1, and the amount of the shaped phase change material added to the final product is 30 to 60 wt%;

[0035] The surface pore structure of the thermal insulation material in step D includes micropores, mesopores and macropores, with a porosity of 70-80% and a density of 0.350-0.400 g / cm 3

[0036] The bark-mineral polymer composite wall material of the present invention has the following advantages:

[0037] 1. The present invention uses pine bark and mineral polymer metakaolin, which are abundant in yield and low in cost, to prepare the bark-mineral polymer composite material, which has excellent thermal insulation and temperature regulation properties, and the raw materials are widely available, low in price, and environmentally friendly;

[0038] 3. The composite foam material prepared by the present invention has an optimal porosity of 74.4%, a density of 0.380 g / cm3, and a thermal conductivity of 0.0733 W / (m·℃), reaching the A04 grade in the industry standard JG / T 266-2011 "Foamed Concrete"; the compressive strength is increased to 1.442 MPa, which is 504% higher than the compressive strength of the foamed mineral polymer, reaching the C1 strength grade specified in the industry standard; the water absorption rate is 43%, which meets the W50 grade in the industry standard; and the noise reduction coefficient (NRC) of this material is 0.80, reaching the Class I sound absorption performance specified in the national standard, and can also be used as a sound absorbing material while keeping warm.

[0039] 4. The phase change temperature of the optimal encapsulated shaped phase change material PEG / C22 prepared by the present invention is 21.6-34.2°C, and the latent heats of melting and crystallization are 74.4J / g and 68.7J / g respectively. The phase change temperature meets the use conditions of wall materials, and the latent heat also meets the theoretical estimated value; the thermal conductivity is 0.943W / (m·℃), which is about 370% higher than that of pure PEG1000; and the secondary encapsulation phase change material further improves the anti-leakage performance, and its latent heat remains 98.05% after 100 thermal cycles, which further extends the product service life while the phase change material forms a certain size. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is a process flow chart of the preparation of the heat-insulating and temperature-regulating artificial board material for the wall of the present invention;

[0041] Figure 2 It is a two-dimensional geometric schematic diagram of the wall thickness section of different model combinations of the embodiment of the present invention and the comparative example; DETAILED DESCRIPTION

[0042] In order to better understand the present invention, the present invention is further described below in conjunction with specific embodiments, and the advantages and features of the present invention will become clearer as the description proceeds. It should be noted that the embodiments are merely exemplary and do not constitute any limitation to the scope of the present invention. It should be understood by those skilled in the art that the details and forms of the technical solution of the present invention may be modified or replaced without departing from the spirit and scope of the present invention, but these modifications and replacements all fall within the scope of protection of the present invention.

[0043] Example 1

[0044] A. Preparation of Geopolymers

[0045] Aluminosilicate was used as a precursor, and 10 mol / L sodium hydroxide solution was used for alkali excitation treatment. The alkali excitation liquid modulus was 1.7 and the alkali-ash ratio was 2.1. After complexation, transfer diffusion, condensation and hardening, a mineral polymer was obtained.

[0046] B. Preparation of mineral polymer foam materials

[0047] 1) Maintenance and foaming

[0048] Add 2.0wt% of 30% hydrogen peroxide, stir for 90s, and cure the mineral polymer in a 60°C oven for 48h, and then cure at room temperature for seven days to fully foam it;

[0049] 2) Strengthening and toughening

[0050] Add alkali-treated bark to the foamed mineral polymer, with a mesh size of 60-100 mesh and an addition amount of 5wt%;

[0051] C. Preparation of bark carbon phase change thermal storage material

[0052] 1) High temperature pyrolysis

[0053] Pine bark was treated by impregnation with 0.25 mol / L KHCO3 solution, and the dried powder was fully ground and pyrolyzed in a tube furnace at a calcination temperature of 600°C and a calcination time of 2 h.

[0054] 2) Immersion fixation

[0055] The pyrolyzed bark carbon was impregnated with polyethylene glycol having a molecular weight of 1000;

[0056] 3) Secondary packaging

[0057] The polyethylene glycol-bark was treated with secondary encapsulation by mineral polymer, and the alkali-activated liquid modulus was 2.1, the alkali-ash ratio was 2.1, and the addition amount of the shape-fixed phase change material was 60wt%;

[0058] D. Bark-Geopolymer Composite Assembly

[0059] The bark-mineral polymer foam insulation material prepared in B is combined with the mineral polymer encapsulated bark carbon shaped phase change thermal storage material prepared in C, and the 10 mm thick phase change thermal storage material is placed outside the 60 mm thick foam insulation material to obtain the bark-mineral polymer composite insulation wall Model-1, as shown in FIG. Figure 2 shown.

[0060] Example 2

[0061] A. Preparation of Geopolymers

[0062] Aluminosilicate was used as a precursor, and 10 mol / L sodium hydroxide solution was used for alkali excitation treatment. The alkali excitation liquid modulus was 1.7 and the alkali-ash ratio was 2.1. After complexation, transfer diffusion, condensation and hardening, a mineral polymer was obtained.

[0063] B. Preparation of mineral polymer foam materials

[0064] 1) Maintenance and foaming

[0065] Add 2.0wt% hydrogen peroxide, and cure the mineral polymer that has been standing for 24 hours in a 60℃ oven for 48 hours, and then cure it at room temperature for seven days to fully foam it;

[0066] 2) Strengthening and toughening

[0067] Add alkali-treated bark to the foamed mineral polymer, with a mesh size of 80 and an addition amount of 5wt%;

[0068] C. Preparation of bark carbon phase change thermal storage material

[0069] 1) High temperature pyrolysis

[0070] Pine bark was treated with 0.25 mol / L KHCO3 solution to obtain dried powder, which was fully ground and pyrolyzed in a tube furnace at a calcination temperature of 600°C and a calcination time of 2 h.

[0071] 2) Immersion fixation

[0072] The pyrolyzed bark carbon was impregnated with polyethylene glycol having a molecular weight of 1000;

[0073] 3) Secondary packaging

[0074] The polyethylene glycol-bark is encapsulated twice with mineral polymer, and the amount of the shape-fixed phase change material added is 60wt%;

[0075] D. Bark-Geopolymer Composite Assembly

[0076] The bark-mineral polymer foam insulation material prepared in B is combined with the mineral polymer encapsulated bark carbon shaped phase change thermal storage material prepared in C, and the 10 mm thick phase change thermal storage material is placed in the middle of the 60 mm thick foam insulation material to obtain the bark-mineral polymer composite insulation wall Model-2, as shown in FIG. Figure 2 shown.

[0077] Example 3

[0078] A. Preparation of Geopolymers

[0079] Aluminosilicate was used as a precursor, and 10 mol / L sodium hydroxide solution was used for alkali excitation treatment. The alkali excitation liquid modulus was 1.7 and the alkali-ash ratio was 2.1. After complexation, transfer diffusion, condensation and hardening, a mineral polymer was obtained.

[0080] B. Preparation of mineral polymer foam materials

[0081] 1) Maintenance and foaming

[0082] Add 2.0wt% hydrogen peroxide, and cure the mineral polymer that has been standing for 24 hours in a 60℃ oven for 48 hours, and then cure it at room temperature for seven days to fully foam it;

[0083] 2) Strengthening and toughening

[0084] Add alkali-treated bark to the foamed mineral polymer, with a mesh size of 80 and an addition amount of 5wt%;

[0085] C. Preparation of bark carbon phase change thermal storage material

[0086] 1) High temperature pyrolysis

[0087] Pine bark was treated with 0.25 mol / L KHCO3 solution to obtain dried powder, which was fully ground and pyrolyzed in a tube furnace at a calcination temperature of 600°C and a calcination time of 2 h.

[0088] 2) Immersion fixation

[0089] The pyrolyzed bark carbon was impregnated with polyethylene glycol having a molecular weight of 1000;

[0090] 3) Secondary packaging

[0091] The polyethylene glycol-bark is encapsulated twice with mineral polymer, and the amount of the shape-fixed phase change material added is 60wt%;

[0092] D. Bark-Geopolymer Composite Assembly

[0093] The bark-mineral polymer foam insulation material prepared in B is combined with the mineral polymer encapsulated bark carbon shaped phase change thermal storage material prepared in C, and the 10 mm thick phase change thermal storage material is placed inside the 60 mm thick foam insulation material to obtain the bark-mineral polymer composite insulation wall Model-3. Figure 2 shown.

[0094] Comparative Example 1

[0095] A. Preparation of Geopolymers

[0096] Aluminosilicate was used as a precursor, and 10 mol / L sodium hydroxide solution was used for alkali excitation treatment. The alkali excitation liquid modulus was 1.7 and the alkali-ash ratio was 2.1. After complexation, transfer diffusion, condensation and hardening, a mineral polymer was obtained.

[0097] B. Preparation of mineral polymer foam materials

[0098] 1) Maintenance and foaming

[0099] Add 2.0wt% hydrogen peroxide, and cure the mineral polymer that has been standing for 24 hours in a 60℃ oven for 48 hours, and then cure it at room temperature for seven days to fully foam it;

[0100] 2) Strengthening and toughening

[0101] Add alkali-treated bark to the foamed mineral polymer, with a mesh size of 80 and an addition amount of 5wt%;

[0102] The bark-mineral polymer foam insulation material prepared in B is taken as a wall with a thickness of 60 mm to obtain a bark-mineral polymer composite insulation wall Model-0 which is not composited with a phase change heat storage material. Figure 2 shown.

[0103] The test results show that:

[0104] Table 1 Performance parameters of thermal insulation materials and heat storage materials

[0107]

[0108] Table 2 Delay time and temperature difference attenuation rate of spring and summer temperature peaks of different wall combinations

[0109]

[0110] 1. The combination of organic and inorganic thermal insulation materials, pure thermal insulation materials play a role

[0111] 2. On the basis of traditional insulation methods, heat storage materials are added to achieve temperature control function.

[0112] 3. The raw materials are widely available and low in price, and the finished products are environmentally friendly, energy-saving and emission-reducing.

Claims

1. A method for preparing a thermal insulation material by using bark and mineral polymer as raw materials, comprising the following steps in order: A. Preparation of Geopolymers Aluminosilicate is used as a precursor, and mineral polymers are obtained through alkali excitation, complexation, transfer diffusion, condensation and hardening. B. Preparation of mineral polymer foam materials 1) Foaming After adding the foaming agent, stir to fully foam the mineral polymer; 2) Strengthening and toughening Adding alkali-treated bark to foamed mineral polymers to enhance strength and toughness; 3) Maintenance Carry out 48h+7d curing treatment on the foamed mineral polymer; C. Preparation of bark carbon phase change thermal storage material 1) High temperature pyrolysis Pine bark was treated with KHCO3 solution to obtain dried powder, which was fully ground and then pyrolyzed in a tube furnace; 2) Immersion fixation The pyrolyzed bark carbon was impregnated with polyethylene glycol; 3) Secondary packaging Secondary encapsulation of PEG-bark with mineral polymers; D. Bark-Geopolymer Composite Assembly The bark-mineral polymer foaming material prepared in B is combined with the mineral polymer encapsulated bark carbon shaped phase change material prepared in C to obtain a bark-mineral polymer composite thermal insulation material.

2. The method according to claim 1, characterized in that the aluminosilicate described in step A is metakaolin, and the alkali activator is prepared by mixing a sodium silicate solution and a 10 mol / L sodium hydroxide solution in proportion.

3. The method according to claim 1, characterized in that The geopolymer modulus of step B1) is 1.3-2.1, the alkali-ash ratio is 1.3-2.5, and the foaming agent is 30% hydrogen peroxide (H2O2) with a mass fraction of 1-3wt%.

4. The method according to claim 1, characterized in that The bark added in step B 2) is coniferous bark, with a moisture content of less than 10%, a mesh size of 60-100 meshes, and a mass fraction of 5wt%.

5. The method according to claim 1, characterized in that The curing conditions in step B3) are curing in a forced air drying oven at a temperature of 60° C. for 48 hours and then curing at room temperature for 7 days.

6. The method according to claim 1, characterized in that The bark used in step C1) has a mesh size of 80-100 meshes and a mass ratio of 1:15-1:20 to a KHCO3 solution having a concentration of 0.25 mol / L, and is calcined at a temperature of 400-800° C. for 2 hours.

7. The method according to claim 1, characterized in that Step C 2) The molecular weight of the PEG polyethylene glycol used for impregnation is 1000, and the mass ratio of the PEG polyethylene glycol to the bark powder is 2:1 to 3:

1.

8. The method according to claim 1, characterized in that In step C 3), the modulus of the mineral polymer material is 1.3-2.1, the alkali-ash ratio is 1.3-2.1, and the amount of the shape-fixed phase change material added in the final product is 30-60wt%.

9. The method according to claim 1, characterized in that the surface pore structure of the thermal insulation material in step D comprises micropores, mesopores and macropores, with a porosity of 70-80% and a density of 0.350-0.400 g / cm.